A phenomenological analysis on the phenomenon of social justice - TUNCEL, GÜL (My University, 2022)
Social justice is generally defined as the fair and equitable distribution of power, resources, responsibilities in society to all people, regardless of race, ethnicity, age, gender, ability, sexual orientation and religious or spiritual background (Van den Bos 2003). The key principles underlying this definition include the values of inclusion, cooperation and solidarity, as well as equal access and equal opportunity. These values are also the foundation of a democratic and egalitarian society (Sue 2001). Therefore, the phenomenon of social justice should be available in all institutions of the society. However, educational institutions in particular, have a significant role in the establishment of social justice. When the education system does not offer equal opportunities and is privileged only for a certain group, it negatively affects a society both culturally and economically. The effort to achieve social justice in education also includes the effort to correct some inequalities in education. In this context, the aim of this research is to try to reveal the social justice/injustice experiences of social studies teacher candidates and to make predictions for social justice education based on these experiences.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); : Social justice; social justice experiences; education; phenomenology